Features of the legal regime of land defense of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
This article displays the legal regime of the use and ownership of land set aside for land defense feature ofsocial relations associated with the use, possession of land defense, a long-term lease on the platform of theStates on the issues of long-term changes in terms of compensated use of land defense.Keywords: Earth Defense, polygon, the legal regime of land use dolgsrochnoe vozmednoe defense.